A citation analysis of the Philippine Journal of Nutrition, 2001-2011 - Sabio, Mae Shaani S.; Golfo, Mary Grace P. (Quezon City : School of Library and Information Studies, University of the Philippines Diliman, 2013)
Journals are effective tools in publicizing updated information, and reflect interactions of information on a certain field of knowledge. This study used citation analysis to identify the current knowledge trends found in the Philippine Journal of Nutrition during the period of 2001-2011. Citation analysis is a practical basis for an effective collection development of libraries. Seventy-eight articles were analyzed and extracted a total of 1,530 citations. Data was encoded into a statistical software and then analyzed through frequency counts and descriptive statistics.
The study revealed the following findings: the most cited bibliographic format in PJN was journal article with 52.5% of the total citations followed by book and book chapter with 16.9% and scientific and technical reports with 6.7%, the most cited journal title was The American Journal of Clinical Nutrition (128 citations of 67.3% of 804 journal articles) followed by Philippine Journal of Nutrition with 56 citations (29.4%) and The Journal of Nutrition with 32 citations or 16.8%. The highly cited title was the Philippine nutrition : facts and figures (10 citations) published by Food and Nutrition Research and Department of Science and Technology. The predominant country of publication was the United States with (39.3%) followed buy literatures published in the Philippines that was cited 363 times (23.7%) and England with 232 titles (15.2%). The most cited author in PJN was the World Health Organization with 70 citations followed by Food and Research Institute with 65 citations and Department Science and Technology with 40 citations. The predominant publishers cited in PJN was American Society of Clinical Nutrition was the most cited with 127 citation (8.3%) followed by WHO with 82 citation (5.4%) and Food Nutrition Research (FNRI) with 60 citation (3.9%). The age of cited materials in PJN was 6 years and for individual year, 1998 was the citation peak. Food and Beverages received the highest frequency as subject of the articles in PJN (12 counts or 15.4%) followed by Technology, Industry and Agriculture (10 counts or 12.8%) and Nutrition Surveys with 9 counts or 11.5%.
Vita.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Philippine Journal of Nutrition; Bibliographical citations; Nutrition -- Periodicals